Potential Natural Fibrous Filter against PM2.5 from Juncus Effuses. Issue 3 (4th March 2022) - Yang, Huiyu; Deng, Hongzhen; Zhai, Lisha; Deng, Bo
ABSTRACT: The internal morphology and micro-pore distribution of Juncus effuses (JE) plant fiber were characterized by scanning electron microscopy (SEM). The porosity parameters and pore size characteristics of JE fiber were measured by a mercury intrusion meter. Fourier transform infrared (FTIR) spectroscopy was used to reveal the chemical composition of JE fiber. Thermal gravimetric analysis (TGA) was used to reveal the thermal degradation behavior of JE fiber. The X-ray diffraction (XRD) technique was used to evaluate the crystal structure of JE fiber. Then the filtration performance of JE filters with lengths of 2.5, 5, 7.5, and 10 cm against particle matter (PM)10, PM2.5, and PM1.0 were compared on a home-made apparatus.